Ontological Dependence and the Metaphysics of Individual Substances, 1540–1716. - Blank, Andreas

“Domingo de Soto on Doubts, Presumptions, and Noncomparative Justice.” - Blank, Andreas (History of Philosophy Quarterly)

“Zabarella and the Early Leibniz on the Diachronic Identity of Living Beings.” - Blank, Andreas (Studia Leibnitiana)

“Mary Astell on Flattery and Self-Esteem.” - Blank, Andreas (The Monist)

“Wittgenstein on Aspect Blindness and Meaning Blindness” - Nachtomy, Ohad; Blank, Andreas (Iyyun. The Jerusalem Philosophical Quarterly)

“Leibniz, Locke, and the Early Modern Controversy over Legal Maxims.” - Blank, Andreas (History of European Ideas)

“Domingo de Soto on Justice to the Poor.” - Blank, Andreas (Intellectual History Review)

“Leibniz and the Early Modern Controversy over the Right of International Mediation.” - Blank, Andreas (“Das Recht kann nicht ungerecht sein …” Beiträge zu Leibniz’ Philosophie der Gerechtigkeit.)

“Archibald Campbell über Gewissen und Kosmopolitismus.” - Blank, Andreas (Gewissen zwischen Gefühl und Vernunft.)

“Presumption and Leibniz’s Metaphysics of Action.” - Blank, Andreas (Leibniz’s Metaphysics and Adoption of Substantial Form.)

Optimum Efficiency Control of Interior Permanent Magnet Synchronous Motors in Drive Trains of Electric and Hybrid Vehicles - Peters, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (European Conference on Power Electronics and Applications (EPE))

“Animals and Immortality in the Monadology.” - Blank, Andreas (Hungarian Philosophical Review)

Späte Suche nach den Gräbern ‒ Claude Simons Auseinandersetzung mit dem Ersten Weltkrieg in L'Acacia - Schreckenberg, Stefan (Lendemains ‒ Études comparées sur la France)

Formate geschlossener Aufgaben zur Messung von Kompetenzen historischen Denkens - Meyer-Hamme, Johannes (Forschungswerkstatt Geschichtsdidaktik 13. Beiträge zur Tagung „geschichtsdidaktik empirisch 13“)

There is not only one worthy way of measuring competencies of historical thinking. - Meyer-Hamme, Johannes (Public History Weekly)

Performance Analysis and Simulation of a Freifunk Mesh Network in Paderborn using B.A.T.M.A.N Advanced - Hardes, Tobias
Free networks are established and maintained by more and more people on a voluntary basis to be independent from commercial providers. This also enables an uncensored communication and leads to a network owned by a community. Freifunk is such a project and it is based on wireless mesh networks. All participants provide an own wifi router (node) for transferring data between different devices. The routing protocol used in the Freifunk network of Paderborn is called Better Approach To Mobile Ad-hoc Networking advanced (B.A.T.M.A.N. IV or Batman-adv). It uses so called Originator Messages (OGM) to announce the existence of a node and to measure the quality of different links in the network. The Freifunk network in Paderborn consists of about 800 nodes that periodically broadcast OGMs. This leads to a substantial base load of ∼25 GByte per month and node. Instead of performing modifications in the real network, I create a simulation model of the current network structure and implement version IV of the B.A.T.M.A.N. routing protocol. The model is validated by using data from the real network. Based on this model I propose and evaluate five different opportunities to improve the base load without impairing other functionality of the network. The simulation results show that a combination of two improvements can lead to a reduction up to 90 %.

Intermediäre Aushandlungsräume. Herausforderung für die Governanceanalyse und grenzüberschreitende Handlungskoordination im BNE-Transfer - Nikel, Jutta; Haker, Christoph (Zeitschrift für Bildungsforschung)

Kann professorale Lehre tutoriell sein? Ein Modellversuch zur Einführung in mathematisches Denken und Arbeiten - Hilgert, Joachim; Hoffmann, Max; Panse, Anja (Tagungsband zum Hansekolloquium zur Hochschuldidaktik der Mathematik.)

Einführung in mathematisches Denken und Arbeiten: tutoriell und transparent - Hilgert, Joachim; Hoffmann, Max; Panse, Anja

Pfade im editorischen Netz. Überlegungen zur Pragmatik des editorischen Hyperlinks am Beispiel der Comédie en vaudevilles Annette et Lubin (1762) - Droese, Janine; Münzmay, Andreas (Editio. Internationales Jahrbuch für Editionswissenschaft)
In creating a Hybrid Edition of Justine Favart’s and Adolphe Blaise’s Annette et Lubin, a ‹comédie en vaudevilles› that premiered in Paris at the Comédie-Italienne in early 1762, for the OPERA series, the authors explore new ways of editing opera by means of XML/Edirom technology. In the light of Patrick Sahle’s account of edition as hypertext (chapter „Edition als Hypertext“ in Digitale Editionsformen, 2013), the paper focusses on the ‹timbre› indications inherent to the literary text, proposes an understanding of the ‹timbres› that is quite close to what we know as hyperlinks in the age of hypertext, and discusses, from a firmly pragmatic standpoint, the editors’ handling of what one might regard as abundance of hyperlinks. Constructing a historical-critical edition implies, of course, all ‘traditional’ tasks of philological groundwork. But beyond this, today, defining the concept of and programming a vast number of digital links are part of an editor’s core activities: editorially controlled representations of connections inherent to the text, both on the philological, and the historical level.
Keywords: Musicology